PENGARUH KUALITAS PRODUK DAN KUALITAS LAYANAN TERHADAP LOYALITAS PELANGGAN DENGAN KEPUASAN PELANGGAN SEBAGAI VARIABLE MEDIASI DI PERUMAHAN PURI KAHURIPAN KARANGANYAR - TITAH SEPTIYANA RACHMATIKA (Riset Manajemen dan Akuntansi, 2016)
Goal of the research is to knowing what satisfaction variabel to mediation influence of service quality and product head to loyalty. The research is to be research with survey method. Population target in the research is Puri Kahuripan Karanganyar customer. Sample that take is 70 people. Analysis method that is used on this research is path analysis. Path analysis is used to test relation cause and effect based on science, theory and assumption can also to this hypothesis testing is done with spss 16. Program to analyze kausalitas relation on structure model that propost. The research result is such as : 1) Quality product is positively and significant effect to satisfaction and loyalty customer of Puri Kahuripan Papahan Karangayar; 2) Customer satisfaction is positively and significant effect to loyalty customer of Puri Kahuripan Papahan Karangayar; 3) The mediation of satisfaction influences product quality variable head to customer loyalty. Keyword : service quality, product quality, satisfaction, loyalty, property